2014
DOI: 10.1016/j.funbio.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of ambrosia beetle symbionts in the genus Raffaelea

Abstract: The genus Raffaelea was established in 1965 when the type species, R. ambrosia, a symbiont of Platypus ambrosia beetles was described. Since then, many additional ambrosia beetle symbionts have been added to the genus, including the important tree pathogens R. quercivora, R. quercus-mongolicae, and R. lauricola, causal agents of Japanese and Korean oak wilt and laurel wilt, respectively. The discovery of new and the dispersal of described species of Raffaelea to new areas, where they can become invasive, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 35 publications
(47 reference statements)
5
32
0
1
Order By: Relevance
“…The phylogenetic placement of these two OTUs were further investigated using βT and CAL Dreaden et al (2014) showed that Raffaelea is not monophyletic as was suggested by Harrington et al (2010). Conidiophores hyaline, (6.6-) 7.1-8.9 (-9.2) µm long, (0.3-) 0.7-1.1 (-1.5) µm wide ( Fig.…”
Section: Beetlesmentioning
confidence: 95%
“…The phylogenetic placement of these two OTUs were further investigated using βT and CAL Dreaden et al (2014) showed that Raffaelea is not monophyletic as was suggested by Harrington et al (2010). Conidiophores hyaline, (6.6-) 7.1-8.9 (-9.2) µm long, (0.3-) 0.7-1.1 (-1.5) µm wide ( Fig.…”
Section: Beetlesmentioning
confidence: 95%
“…These analyses are aided by recently published phylogenies of Raffaelea [101,102], which have identified the closest, extant relatives of R. lauricola; notably, all other members of the phylogenetic clade in which R. lauricola resides (Raffaelea sensu stricto) are not plant pathogens. Of particular interest are genome-wide comparisons between R. lauricola and its close relative R. aguacate D. R. Simmons, Dreaden and Ploetz.…”
Section: Pathogen Attributesmentioning
confidence: 99%
“…The family represents some of the earliest angiosperms and has a fossil record dating back to the Mid-Cretaceous [105]. It is well represented on both sides of the Pacific Basin, and the so-called "amphi-Pacific tropical disjunction" of the Persea and Cinnamomum groups in the family has been examined to understand the presence, and the origins and relatedness, of family members in the Eastern and Western Hemispheres [101,106,107].…”
Section: Hosts Of Laurel Wiltmentioning
confidence: 99%
“…Harrington et al 2010). However, more recent and comprehensive analyses (de Beer & Wingfield 2013, Dreaden et al 2014, Musvuugwa et al 2015) have shown that Raffaelea species constitute three clades in the order, Raffaelea s. str. , the R. lauricola complex, and the R. sulphurea complex.…”
Section: Introductionmentioning
confidence: 99%
“…Raffaelea lauricola, the eponymous member of the R. lauricola complex (de Beer & Wingfield 2013, Musvuugwa et al 2015), is sometimes placed as sister to Raffaelea s str. in molecular phylogenies of individual rDNA loci (Musvuugwa et al 2015) and additional coding genes (Dreaden et al 2014). Raffaelea quercivora , which is responsible for Japanese oak wilt and associated with Platypus quercivorus (Kubono & Ito 2002, Kusumoto et al 2014), lies within the R. sulphurea complex in Leptographium s. lat.…”
Section: Introductionmentioning
confidence: 99%